Alexandre Magno caçador de leões - Thiago Amaral Biazotto (Figura, 2020)
This article argues in favor of a connection between the Craterus' ex-voto at Delphi and the Pella Mosaic, that shows a lion hunting scene with two hunters. It seeks to demonstrate that the mosaic is a copy of the original sculptures, made by Lysippos and Leochares, and, moreover, that the House of Dionysus may have belonged to Craterus' family.